OP19 Corticosteroid response rectal gene signature and associated microbial variation in treatment naïve ulcerative colitis. (25th January 2019) - Haberman, Y; Karns, R; Dexheimer, P; Schirmer, M; Braun, T; Collins, M; Mo, A; Rosen, M; Gotman, N; Kugathasan, S; Walters, T D; et al.
Abstract: Background: Molecular mechanisms driving disease course and response to initial therapy in ulcerative colitis (UC) are poorly understood. In the full PROTECT cohort, the strongest predictor of corticosteroids (CS)-free remission by Weeks 12 or 52 was Week 4 (WK4) remission. We used pre-treatment rectal biopsies in new-onset UC, and defined key pathways linked to WK4 response to standardised induction with CS in the largest prospective paediatric UC cohort to date. Methods: PROTECT enrolled 428 newly diagnosed paediatric UC patients at 29 North American sites. mRNA-Seq and 16S rRNA defined pre-treatment rectal gene expression and microbial communities in 206 participants. Independent group of 50 participants were used to validate the CS response gene signature. WK4 remission was defined as PUCAI < 10 without additional therapy/colectomy. Results: Moderate–severe UC patients (152/206) from the discovery cohort and all 50 from the validation cohort received standardised induction therapy with CS. WK4 remission was achieved in 75/152 (49%) and 21/50 (42%) of the discovery and validation groups respectively. 115 genes were differentially expressed (FDR<0.05 and FC ≥1.5) between moderate–severe UC patients who did or did not achieve WK4 remission in the discovery cohort. The corticosteroid response gene signature is highly associated with CXCR chemokines ( p < 7.12E−12), innate myeloid immune signatures ( p < 1.62E−15), and response to bacteria ( p < 2.16E−13). Principle component analyses (PCA) PC1 that summarise the variation of the CS response signature, was significantly different between those that achieved WK4 clinical remission ( p < 0.001) and mucosal healing ( p = 0.002) defined as faecal calprotectin < 250 μg/g in the discovery cohort. This was replicated in the independent validation cohort, and was also associated with response to anti-TNFα and anti-α4β7 integrin induction in adults. The response gene signature was associated with shifts in microbes previously implicated in mucosal homeostasis; positive association with taxa such as Campylobacter, Veillonella, and Enterococcus implicated in mucosal inflammation, and a negative association with taxa from the Clostridiales order that are considered beneficial. Finally, the addition of the pre-treatment rectal gene signature PC1 [OR = 0.4 (0.2–0.8 95% CI)] improved WK4 clinical prediction model of remission with CS [AUC = 77.7 (70.0–85.4 95% CI)]. Conclusions: We identified a gene signature linked to WK4 CS response, which was validated in independent UC patients, and showed associations with response to anti-TNFα and anti-α4β7 integrin in adults, and with specific microbial taxa. Our data may prioritise future therapies for non-responders to current approaches.